2021
DOI: 10.1093/cid/ciab745
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Genomic Data to Characterize Endemic Typhoid Transmission

Abstract: Background Diverse environmental exposures and risk factors have been implicated in the transmission of Salmonella Typhi, however, the dominant transmission pathways through the environment to susceptible humans remain unknown. Here, we utilize spatial, bacterial genomic, and hydrological data to refine our view of Typhoid transmission in an endemic setting. Methods 546 patients presenting to Queen Elizabeth Central Hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Use of the same passive surveillance protocols across all sites, in defined study catchments and including all ages, allows the results to be compared between sites. The genotype prevalences we estimated are in line with other studies of enteric fever pathogens reported from the same cities 2, 3, 7–10, 21, 25, 26 , but we also specifically addressed pathogen diversity across age groups. We show that although the disease burden is highest in children 20 , the same pathogen variants (serovars, genotypes, and AMR) circulate across age groups (pre-school, school-age, and adult), with near-identical sequences (0-SNV clusters) identified across age groups ( Figs.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Use of the same passive surveillance protocols across all sites, in defined study catchments and including all ages, allows the results to be compared between sites. The genotype prevalences we estimated are in line with other studies of enteric fever pathogens reported from the same cities 2, 3, 7–10, 21, 25, 26 , but we also specifically addressed pathogen diversity across age groups. We show that although the disease burden is highest in children 20 , the same pathogen variants (serovars, genotypes, and AMR) circulate across age groups (pre-school, school-age, and adult), with near-identical sequences (0-SNV clusters) identified across age groups ( Figs.…”
Section: Discussionsupporting
confidence: 70%
“…The Blantyre study area has a complex river system, comprising 10 river catchments in close proximity, and recent spatial modelling of S . Typhi sequences in this setting showed that dividing space into river catchments explained the spatio-genetic patterns much better than simple grid coordinates 26 . Detailed spatial modelling is beyond the scope of this study but is planned for all STRATAA sites.…”
Section: Discussionmentioning
confidence: 83%
“…Our results indicate that rpoS is likely to play an important role in surviving this transition. In addition, since S. Typhi does not productively infect animals other than humans, it may have to exist for extended periods in wells, ponds, rivers and other freshwater collections that represent sources of infection in parts of the world where typhoid is endemic [20][21][22][23]. Thus, S. Typhi may be particularly dependent on rpoS for survival in such environments, raising the possibility that targeting this gene or its downstream functions could represent a strategy for interfering with transmission of the pathogen.…”
Section: Plos Onementioning
confidence: 99%
“…This requirement may be particularly relevant to S. Typhi, which does not have a non-human animal host that can act as an intermediary in transmitting infection. Although direct fecal-oral transmission of S. Typhi between humans may occur, indirect transmission via consumption of untreated water from wells, ponds and rivers probably plays an even more important role [20][21][22][23]. Thus, the pathogen must have the ability to adjust to and tolerate the low osmolarity of such freshwater sources.…”
Section: Introductionmentioning
confidence: 99%
“…The transmission of S. Typhi is classified into two patterns. Short-cycle transmission refers to the contamination of food and water sources by shedding of the bacterium through feces in the immediate environment or close proximity, which facilitates transmission through poor hygiene and sanitation practices, and is generally linked to food handlers [ 7 ]. Long-cycle transmission occurs when the broader environment (such as untreated water or sewage) is polluted with human feces or when it is used as a raw fertilizer for crops [ 8 ].…”
Section: Introductionmentioning
confidence: 99%